Respuesta :
ANSWER
[tex]f(5)=7.5[/tex]
EXPLANATION
The recursive definition is
[tex]f(n+1)=-0.5f(n)[/tex].
Since the first term of the sequence is given to us, we need to plug in [tex]n=1[/tex].
This implies that;
[tex]f(1+1)=-0.5f(1)[/tex].
[tex]f(2)=-0.5f(1)[/tex]
But we were given that, [tex]f(1)=120[/tex].
This implies that;
[tex]f(2)=-0.5\times 120[/tex]
[tex]f(2)=-60[/tex]
Since we now know that [tex]f(2)=-60[/tex], we again plug in [tex]n=2[/tex] in to the recursive definition.
[tex]f(2+1)=-0.5f(2)[/tex]
[tex]\Righarrow f(3)=-0.5\times -60[/tex]
[tex]\Righarrow f(3)=30[/tex].
We plug [tex]n=3[/tex] in to the formula again to determine the 4th term.
[tex]f(4)=-0.5f(3)[/tex].
[tex]f(4)=-0.5 \times 30[/tex]
[tex]f(4)=-15[/tex].
We finally find the 5th term by substituting [tex]n=4[/tex].
[tex]f(4+1)=-0.5f(4)[/tex]
[tex]f(5)=-0.5\times (-15)[/tex]
[tex]f(5)=7.5[/tex]